Perspective on dysphagia screening, assessment methods, and protocols in intensive care units: an opinion article - Demetriou, Maria; Georgiou, Anastasios M. (My University, 2024)
Intensive care unit (ICU) admission and related prolonged intubation has been identified as a substantial risk factor for the development of swallowing problems (aka dysphagia) (Perren et al., 2019; Spronk et al., 2022; Royals et al., 2023). Indeed, postextubation dysphagia (PED) has a documented prevalence rate of 93% (Macht et al., 2013) and has been linked to adverse health outcomes and risks, including aspirationrelated pneumonia (Barker et al., 2022; Freeman-Sanderson et al., 2023; Royals et al., 2023), malnutrition (Barker et al., 2022; Royals et al., 2023), dehydration (Royals et al., 2023), re-intubation (Muñoz-Garach et al., 2023; Royals et al., 2023), prolonged mechanical ventilation (MV) and length of ICU/hospital stay (Barker et al., 2022; Muñoz-Garach et al., 2023; Royals et al., 2023; Clayton et al., 2024). Additionally, it contributes to delayed recovery (Royals et al., 2023), reduced quality of life (QoL), and higher short-term (28 days) and mid-term (90 days) mortality rates (Perren et al., 2019; Muñoz-Garach et al., 2023; Clayton et al., 2024). Despite being prevalent and clinically significant in the ICU, PED remains underrecognized due to minimal routine screening (Zurbano et al., 2023) and a lack of comprehensive assessment guidelines (Likar et al., 2024). Fewer than thirty percent of surveyed ICU practitioners employ dysphagia protocols, while less than 20% of nurses undergo formal dysphagia training regarding the screening of patients for suspected PED (Freeman-Sanderson et al., 2023). But dysphagia screening and thereafter assessment is particularly crucial for its early identification, management, prevention and mitigation of complications, optimization of nutritional support and ultimately enhancement of patient overall health outcomes (Freeman-Sanderson et al., 2023; Mpouzika et al., 2023; Troll et al., 2023; Zurbano et al., 2023).
Keywords: screening tools; assessment practices; dysphagia; intensive care unit (ICU); protocol and guidelines